Analisis Kepuasan Pengguna Sistem VANESA Menggunakan Technology Acceptance Model (TAM) - Novita Nuraini; Rossalina Adi Wijayanti; Andri Permana Wicaksono; Niyalatul Muna (Politeknik Negeri Jember, 2026)
The development of digital technology has driven innovation in the provision of nutrition education and consultation services, one of which is through the implementation of the VANESA (Virtual Assistant Nutritional Care Center for Education and Consultation) system. This study aims to analyze user satisfaction with the VANESA system using the Technology Acceptance Model (TAM) approach, which emphasizes two main variables, namely perceived usefulness and perceived ease of use, as the main determinants of technology acceptance. This study uses a quantitative method with a survey approach to active VANESA users. Data was analyzed using regression analysis techniques and validity tests to examine the relationship between variables in the TAM model and the level of user satisfaction. The results show that both perceptions of usefulness and ease of use have a positive and significant influence on user attitudes, which in turn impacts their satisfaction with the use of the VANESA system. These findings indicate that increasing the functionality and ease of access of the system will strengthen user acceptance. This study provides important implications for the development of digital healthcare systems, particularly in designing virtual assistants that are adaptive to user needs and based on user experience.Keywords: nutrition education, satisfaction, TAM, VANESA